Sendo a equação biquadrada 5+x^4-6x^2=0
Soluções para a tarefa
Respondido por
1
5 + x⁴ - 6x² = 0
(x²)² - 6x² + 5 = 0
Let x² = y:
y² - 6y + 5 = 0
y² - y - 5y + 5 = 0
y( y - 1 ) - 5( y - 1 ) = 0
( y - 1 )( y - 5 ) = 0
y' = 1
y" = 5
_________
y = x²
• x² = 1 → x' = ± 1
• x² = 5 → x" = ±√5
_________
S = { -√5, -1, 1, √5 }
(x²)² - 6x² + 5 = 0
Let x² = y:
y² - 6y + 5 = 0
y² - y - 5y + 5 = 0
y( y - 1 ) - 5( y - 1 ) = 0
( y - 1 )( y - 5 ) = 0
y' = 1
y" = 5
_________
y = x²
• x² = 1 → x' = ± 1
• x² = 5 → x" = ±√5
_________
S = { -√5, -1, 1, √5 }
Perguntas interessantes
Matemática,
10 meses atrás
Matemática,
10 meses atrás
Matemática,
10 meses atrás
Matemática,
1 ano atrás
Administração,
1 ano atrás
Matemática,
1 ano atrás